Acute dental pain and the different management methods among adults in Taif, Saudi Arabia: A cross-sectional study - Bandar S. Shukr; Ayman Mandorah; Faisal K. Altalhi; Yousef A. Alqurashi; Hassan T. Shawli; Ali A. Alqarni; Mohammed A. Alzubaidi (Saudi Journal of Oral Sciences)
Introduction: One of the most common reasons for visiting dental clinics is dental pain. Seeking timely and professional dental care is a crucial step to maintain good oral health. Aims: The aim of the present study was to explore the prevalence of acute dental pain, the different management methods, and the use and practicality of teledentistry and online dental consultations among the population of Taif, Saudi Arabia. Materials and Methods: A total of 556 adults were enrolled in the study by answering an online survey that was distributed through different social media websites. Data were collected on the type of dental pain, pain-related characteristics using the Modified Dental Pain Screening Questionnaire, self-and formal care methods for pain relief, and the utilization of teledentistry services. Data analysis was performed using descriptive statistics, the Chi-square test, and the logistic regression model. Results and Discussion: Of the 556 participants, approximately 68% reported having dental pain, and almost 39% reported that the pain originated from a tooth. In addition, 73.2% reported that the pain was exacerbated after eating/drinking something cold. Regarding self-care methods, prescribed drugs were found to be mostly taken by those aged 41–50 years (adjusted odds ratio [AOR] = 3.38, P = 0.01), whereas nonprescribed drugs and home remedies were mostly taken by those aged 51 years or older (AOR = 2.25, P = 0.02; AOR = 2.65, P = 0.007; respectively). For formal-care methods, those who obtained professional help to control their pain were more likely to be dentists/dental students (AOR = 6.17, P = 0.02). Furthermore, a borderline effect was observed regarding teledentistry usage, with most users who were connected to a dentist being 31–40 years old (P = 0.09) and less likely to be men (P = 0.08). Conclusion: The prevalence of acute dental pain and self-medication practices was notably high among the study population. Therefore, it is imperative to educate the general public on appropriate management strategies for this type of pain. In addition, the utilization of teledentistry services was minimal within this population.